2021
DOI: 10.1007/s11250-021-02894-x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Aloe vera extract in lactating goats’ diet: effects on rumen fermentation efficiency, nutrient utilization, lactation performance, and antioxidant status

Abstract: The present work was conducted to investigate the effects of supplementing aloe vera extract on rumen fermentation e ciency, nutrient utilization, lactation performance and antioxidant status of goats. Twenty-four crossbreed lactating goats (Alpine × Beetal) were divided into three experimental groups (AV0, AV2 and AV4). AV0 had no supplementation, group AV2 and AV4 received ready to feed aqueous extract of aloe vera at 20 and 40 g/kg dry matter intake, respectively, along with basal diet and experiment lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In ruminants, GAA supplementation increases the apparent digestibility of DMI, OM, CP, NDF and ADF (Liu & Chen et al., 2021 ; Li et al., 2020 ). In addition, betaine supplementation is associated with increased apparent digestibility of DMI, OM and CP in fattened cattle as well as significantly increased apparent digestibility of nutrients in goats (Wafaa & Reham, 2023 ; Wang et al., 2020 ). In the present study, we found that GAA and RPB supplementation improved the apparent digestibility of EE and phosphorus in the first and second parts of the experiment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants, GAA supplementation increases the apparent digestibility of DMI, OM, CP, NDF and ADF (Liu & Chen et al., 2021 ; Li et al., 2020 ). In addition, betaine supplementation is associated with increased apparent digestibility of DMI, OM and CP in fattened cattle as well as significantly increased apparent digestibility of nutrients in goats (Wafaa & Reham, 2023 ; Wang et al., 2020 ). In the present study, we found that GAA and RPB supplementation improved the apparent digestibility of EE and phosphorus in the first and second parts of the experiment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation was a mixture of natural and nature-identical EO compounds, including thymol, eugenol, vanillin, guaiacol, and limonene, bound to a specific organic-inorganic carrier containing benzoic acid, which ensured high stability of the effective components during storage and feed processing. However, the inclusion of Aloe vera extract at 20 and 40 g/kg DMI in the diet of lactating goats improved milk yield, enhanced antioxidant status, and increased rumen fermentation efficiency, with no negative effects on DMI and nutrient utilization [80]. The erythrocyte antioxidant enzyme activity and ferric-reducing total antioxidant power were higher after the use of Aloe vera extract, which resulted in an improvement in the antioxidant status of goats, thus increasing lactation performance; particularly, the best response was achieved with the supplementation of Aloe vera at 40 g/kg DMI.…”
Section: Effects Of Essential Oils On Small Ruminant Productsmentioning
confidence: 96%
“…The erythrocyte antioxidant enzyme activity and ferric-reducing total antioxidant power were higher after the use of Aloe vera extract, which resulted in an improvement in the antioxidant status of goats, thus increasing lactation performance; particularly, the best response was achieved with the supplementation of Aloe vera at 40 g/kg DMI. Goats supplemented with Aloe vera had increased milk production, fat, and protein content of milk by about 6% [80]. Very few studies investigated the effects of EO on milk components and milk fatty acid (FA) composition.…”
Section: Effects Of Essential Oils On Small Ruminant Productsmentioning
confidence: 99%